2021
DOI: 10.1097/mej.0000000000000863
|View full text |Cite
|
Sign up to set email alerts
|

Agreement and validity of electronic patient self-triage (eTriage) with nurse triage in two UK emergency departments: a retrospective study

Abstract: Background Triage and redirection of patients to alternative care providers is one tool used to overcome the growing issue of crowding in emergency departments (EDs). Electronic patient self-triage (eTriage) may reduce waiting times and required face-to-face contact. There are limited studies into its efficacy, accuracy and validity in an ED setting.Objectives The aim of this study was to assess the agreement and validity of eTriage with a reference standard of nurse face-to-face triage. A secondary aim was to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
38
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(47 citation statements)
references
References 24 publications
0
38
0
Order By: Relevance
“…Research examining safety and accuracy of these systems highlights the persistence of a risk-averse disposition (12,(15)(16)(17). An effort is being made to evolve to more balanced algorithms, but some studies report that this evolution currently comes at the expense of the technology's safety, which should always remain their priority (19)(20)(21).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Research examining safety and accuracy of these systems highlights the persistence of a risk-averse disposition (12,(15)(16)(17). An effort is being made to evolve to more balanced algorithms, but some studies report that this evolution currently comes at the expense of the technology's safety, which should always remain their priority (19)(20)(21).…”
Section: Discussionmentioning
confidence: 99%
“…Digital triage services are generally considered risk averse (15)(16)(17), favoring sensitivity over specificity, often over-triaging, assigning a higher urgency level than is required. A systematic review by Chambers et al (12) concluded that the available studies reported no evidence of a detrimental effect on patient safety in both simulated and real settings.…”
Section: Safetymentioning
confidence: 99%
“…Candidate variables have been identified based on expert opinions as well as relevant literature [18,30,[34][35][36]. Moreover, we have sought input from clinicians and informaticians familiar with the raw data to determine which features are feasible to extract and construct from the sources.…”
Section: Variable Constructionmentioning
confidence: 99%
“…When applied in emergency department settings, symptom checkers were reported to be inadequately sensitive to emergency cases, with triage accuracy between 45%-75% of total patients [ 27 - 30 ]. However, in a recent study using digital patient self-triage in a hospital emergency department, a digital tool showed higher sensitivity to high-acuity conditions and similar specificity for low-acuity conditions when compared with standard nurse triage using the Manchester Triage System; it also tended to result in overtriage of patients when compared with standard nurse triage [ 31 ].…”
Section: Existing Evidence On Triage Errorsmentioning
confidence: 99%